1995
DOI: 10.1007/bf00232684
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular pH modulates the Ca2+ current activated by depletion of intracellular Ca2+ stores in human macrophages

Abstract: Intracellular Ca2+ (Ca(i)) signaling following the binding of surface receptors activates a Ca2+ permeable plasma membrane conductance which has been shown to be associated with store depletion in a number of cell types. We examined the activation of this conductance in human monocyte-derived macrophages (HMDMs) using whole-cell voltage-clamp techniques coupled with fura-2 microfluorimetry and characterized the importance of external pH (pHo) as a modulator of current amplitude. Current activation was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 22 publications
5
36
1
Order By: Relevance
“…Similarities were seen in both activation and inactivation kinetics, high sensitivity to 4-AP and relative insensitivity to TEA and DTX ( Table 2). The resemblance in the kinetics of clofilium block of I4o (Amos, Li, Wettwer, Himmel, Metzger & Ravens, 1995) and Kv1.5 channels Malayev, Nelson & Philipson, 1995) provides further evidence. Due to the sensitivity of Kv1.6 channels to TEA, DTX and CTX (Grupe et al 1990) and of I8K to La3+ (Hice et al 1994), these channels are not I4o equivalents.…”
Section: Discussionmentioning
confidence: 88%
“…Similarities were seen in both activation and inactivation kinetics, high sensitivity to 4-AP and relative insensitivity to TEA and DTX ( Table 2). The resemblance in the kinetics of clofilium block of I4o (Amos, Li, Wettwer, Himmel, Metzger & Ravens, 1995) and Kv1.5 channels Malayev, Nelson & Philipson, 1995) provides further evidence. Due to the sensitivity of Kv1.6 channels to TEA, DTX and CTX (Grupe et al 1990) and of I8K to La3+ (Hice et al 1994), these channels are not I4o equivalents.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, in preliminary experiments we found that BAPTNAM, a cell-permeant intracellular Ca2+ chelator, mediated concentration-dependent activation of caspase-3-like proteases and provided no protection against thapsigargin-mediated cell death in SH-SY5Y cells (unpublished data). BAPTA also depletes intracellular Ca2+ stores by chelating Ca2+,, which has leaked from intracellular stores and prevents refilling of the stores (Malayev and Nelson, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…To preclude these possibilities, we examined the effect of reducing extracellular pH on the Ca 2ϩ entry activated by thapsigargin and by arachidonic acid. Modest reductions in extracellular pH have been shown to have a profound inhibitory effect on capacitative Ca 2ϩ entry in a range of different cell types (23)(24)(25)(26), and in the case of the storeoperated channel I CRAC , this has been shown to reflect a direct action of extracellular protons on the channel (27). 2 As shown in Fig.…”
Section: Arachidonate-mediated Ca 2ϩ Entry In Hek293 Cellsmentioning
confidence: 99%